Digital Data Sources and Their Impact on People's Health: A Systematic Review of Systematic Reviews - Li, Lan; Novillo-Ortiz, David; Azzopardi-Muscat, Natasha; Kostkova, Patty (Frontiers in Public Health, 2021)
Background: Digital data source has become a pervasive part of modern culture in the ear of digital technology, and we need to investigate them with traditional data to gain a comprehensive understanding of their impact and benefits on human health. Objective: A systematic review of systematic reviews on digital data sources and their impact on people’s health including challenges, opportunities, and good practices. Methods: A multi-database search was performed. Peer-reviewed papers published between January 2010 and November 2020 relevant to the digital data source on health were extracted, assessed, and reviewed. Results: The 64 reviews are covered in three domains, including Universal Health Coverage (UHC), public health emergencies, and healthier population, defined in the General Programme of Work 2019/2023 and the European Programme of Work 2020/2025 by WHO. In all three categories, social media is the most popular digital data source which accounts for 47% (N = 8), 84% (N = 11) and 76% (N = 26) of studies respectively. The second most utilized data source is electronic health records (EHR) (N=13), followed by the website (N=7) and mass media (N=5). In all three categories, the most studied impact of digital data sources is on the prevention, management, and intervention of diseases (N = 40), and as a tool, there are also many studies (N = 10) on the early warning of infectious diseases. However, they also could be health hazards (N = 13), such as exacerbating mental health issues and promoting smoking and drinking behavior among young people. Conclusions: The demonstrate digital data sources are essential for collecting and mining information about human health. The key impact of social media, EHR, and websites lies in the domain of infectious disease and early warning systems, and for personal health, that is on mental health and smoking and drinking prevention. However, future research is required to address privacy, trust, transparency, and interoperability to leverage the potential of data held in multiple data stores and systems. This study also identified the apparent gap in systematic reviews investigating different digital data sources, as in this domain systematic reviews are not commonplace.